Hemoperfusion: technical aspects and state of the art - Ronco, Claudio; Bellomo, Rinaldo (Critical care (London, England), 2022)
Background Blood purification through the removal of plasma solutes by adsorption to beads of charcoal or resins contained in a cartridge (hemoperfusion) has a long and imperfect history. Developments in production and coating technology, however, have recently increased the biocompatibility of sorbents and have spurred renewed interest in hemoperfusion. Methods We performed a narrative assessment of the literature with focus on the technology, characteristics, and principles of hemoperfusion. We assessed publications in ex vivo, animal, and human studies. We synthesized such literature in a technical and state-of-the-art summary. Results Early hemoperfusion studies were hampered by bioincompatibility. Recent technology, however, has improved its safety. Hemoperfusion has been used with positive effects in chronic dialysis and chronic liver disease. It has also demonstrated extraction of a variety of toxins and drugs during episodes of overdose. Trials with endotoxin binding polymyxin B have shown mixed results in septic shock and are under active investigation. The role of non-selective hemoperfusion in sepsis or inflammation remains. Although new technologies have made sorbents more biocompatible, the research agenda in the field remains vast. Conclusion New sorbents markedly differ from those used in the past because of greater biocompatibility and safety. Initial studies of novel sorbent-based hemoperfusion show some promise in specific chronic conditions and some acute states. Systematic studies of novel sorbent-based hemoperfusion are now both necessary and justified.